Multilevel Modeling of Science Achievement in the TIMSS Participating Countries - Mohammadpour, Ebrahim; Shekarchizadeh, Ahmadreza; Kalantarrashidi, Shojae Aldin (The Journal of educational research (Washington, D.C.), 2015)
The author aimed to investigate the variability in science achievement as a function of student-, school- and country-level factors. Achievement scores of 134,123 eighth-grade students from 4,511 schools of 29 countries who participated in the 2007 Trends in International Mathematics and Science Study were analyzed. Multilevel modeling results showed that science achievement was driven largely by student-level factors. Students scored higher when they had more self-confidence in learning science, came from home with a higher level of family background, were boys, spent less time on nonacademic activities, and did job at home. Schools averaged higher when they had positive school climate, were located in urban areas, and there was no problem with attendance at school and shortages in resources for science instruction.